Transoral incisionless fundoplication and open hiatal hernia repair: A case report - Turaga, Anjani H.; Salem, Yasser H. (Frontiers in Gastroenterology, 2023)
INTRODUCTION: Transoral incisonless fundoplication is a new procedure that has recently emerged as a potential alternative to traditional anti-reflux surgeries. Hiatal hernia repair is also commonly performed in conjunction with transoral incisionless fundoplication to improve outcomes. In this case, it details a successful transoral incisionless fundoplication and hiatal hernia repair procedure in a patient with long standing gastroesophageal reflux disease (GERD). The case is unique as it involved a patient with an uncharacteristically large hiatal hernia measuring above 5cm, which is a size that is generally not considered suitable for transoral incisionless fundoplication. The hiatal hernia was repaired with a gastrectomy instead of laparoscopically due to the size and adhesions present. CASE DETAILS: This case report presents an 86 year old female patient with a history of long-standing GERD symptoms from the past 10 years who had failed to respond to medical therapy. Endoscopic imaging revealed a hernia of more than 5cm in size. A Demeester score of 446 was reported. Despite the large size of the hiatal hernia, it was decided to proceed with a transoral incisionless fundoplication (TIF) procedure combined with hiatal hernia repair. The esophagus was fibrosed to the pericardium, and the stomach was stuck in a retrocardiac position. Laparoscopic removal of the adhesions proved difficult since the patient had friable tissues, and there was a high risk of injury to surrounding organs. The surgery was therefore converted to an open approach, and the hernia was repaired with a gastrectomy. The TIF procedure was performed successfully, and the patient had no complications postoperatively. CONCLUSION: This case details a successful transoral incisionless fundoplication(TIF) procedure for GERD in a patient with an uncharacteristically large hiatal hernia. Despite the challenges posed by the hernia's size and anatomical distortion, the TIF procedure combined with hiatal hernia repair was successful in providing relief from GERD symptoms, with no postoperative complications. The case highlights the potential suitability of TIF as an alternative to laparoscopic fundoplication in patients with large hiatal hernias, although gastrectomy may be necessary in cases with significant adhesions or anatomical distortion.